Positive electrode active material for rechargeable lithium battery, positive electrode including the same, and rechargeable lithium battery including the positive electrode
By using a positive electrode active material layer composed of olivine structure particles and spinel structure particles, the problems of insufficient energy density and life characteristics of rechargeable lithium batteries are solved, and high energy density and enhanced life characteristics are achieved.
Patent Information
- Application Number
- CN202510522176.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-24
- Filing Date
- 2025-04-24
- Publication Date
- 2025-10-24
AI Technical Summary
The energy density and lifespan characteristics of existing rechargeable lithium batteries are insufficient to meet the demands of the rapidly increasing popularity of electronic devices and electric vehicles.
A positive electrode active material composed of olivine structure particles represented by Chemical Formula 1, spinel structure particles represented by Chemical Formula 2, and compound particles represented by Chemical Formula 3 is used in combination with a conductive material and a binder to form a high-efficiency positive electrode active material layer.
Improves the energy density and lifespan characteristics of rechargeable lithium batteries, providing economical and efficient battery performance.
Smart Images

Figure CN120834170A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2024-0054514 filed in the Korean Intellectual Property Office on April 24, 2024, the entire contents of which are incorporated herein by reference. Technical Field
[0003] One or more embodiments of the present disclosure relate to a positive electrode active material for a rechargeable lithium battery, a positive electrode including the positive electrode active material, and a rechargeable lithium battery including the positive electrode, for example, a positive electrode active material including an olivine-based lithium compound, a positive electrode including a positive electrode active material including an olivine-based lithium compound, and a rechargeable lithium battery including the positive electrode. Background Art
[0004] Recently, with the rapid popularization and mass adoption of battery-based electronic devices (such as mobile phones and / or laptop computers) and / or electric vehicles, the demand for rechargeable batteries with relatively high energy density and high capacity has rapidly increased. Accordingly, research and development efforts to improve the performance of such rechargeable batteries (such as rechargeable lithium batteries) are being actively and intensively conducted.
[0005] Rechargeable lithium batteries are batteries that include a positive electrode and a negative electrode (each of which contains an active material capable of intercalating and deintercalating lithium ions) and an electrolyte. When lithium ions are intercalated and deintercalated into and from the positive and negative electrodes, electrical energy is generated through oxidation and reduction reactions. For example, electrical energy is generated when lithium ions are intercalated into and / or deintercalated from the negative electrode during the discharge process. Summary of the Invention
[0006] One or more aspects of embodiments of the present disclosure relate to positive electrode active materials that are economical and have high energy density and enhanced (excellent or adequate) lifespan characteristics.
[0007] One or more aspects of embodiments of the present disclosure are directed to a rechargeable lithium battery that is economical and has high energy density and enhanced (excellent or appropriate) lifespan characteristics by including a positive electrode active material.
[0008] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the presented embodiments of the disclosure.
[0009] According to one or more embodiments of the present disclosure, the positive electrode active material can include a plurality of first particles each including a compound represented by Chemical Formula 1 and having an olivine structure, a plurality of second particles each including a compound represented by Chemical Formula 2 and having a spinel structure, and a plurality of third particles each including a compound represented by Chemical Formula 3. The first particles and the second particles can constitute a main active material. The content (e.g., amount) of the main active material can be about 95 parts by weight to about 99.5 parts by weight, based on about 100 parts by weight of the positive electrode active material, and the content (e.g., amount) of the third particles can be about 0.5 parts by weight to about 5 parts by weight, based on about 100 parts by weight of the positive electrode active material.
[0010] Chemical Formula 1
[0011] Li a1 Fe x1 B 1 y1 PO 4-b1
[0012] In Chemical Formula 1, 0.8≤a1≤1.2, 0.95≤x1≤1.0, 0≤y1≤0.05, 0≤b1≤0.05, x1+y1=1, and B 1 may be at least one element selected from the group consisting of Al, Ti, V, and Mg.
[0013] Chemical Formula 2
[0014] Li a2 Mn x2 C 1 y2 O 4-b2
[0015] In Chemical Formula 2, 0.8≤a2≤1.2, 1.9≤x2≤2.05, 0≤y2≤0.05, 0≤b2≤0.05, and C 1 may be at least one element selected from the group consisting of Al and Mg.
[0016] Chemical Formula 3
[0017] Li a3 Co x3 D 1 y3 O 4-b3
[0018] In Chemical Formula 3, 5.9<a3≤6.1, 0.9≤x3≤1.05, 0≤y3≤0.05, 0≤b3≤0.05, and D 1 may be at least one element selected from the group consisting of Al and Mg.
[0019] According to one or more embodiments of the present disclosure, a positive electrode for a rechargeable lithium battery can include a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector. The positive electrode active material layer can include a positive electrode active material, a conductive material, and a binder.
[0020] According to one or more embodiments of the present disclosure, a rechargeable lithium battery can include a positive electrode active material. BRIEF DESCRIPTION OF DRAWINGS
[0021] The accompanying drawings are included to provide a further understanding of the present disclosure, and are incorporated in and constitute a part of this specification. The drawings illustrate embodiments of the present disclosure and, together with the description, serve to explain the principles of the present disclosure. The above and other aspects, features, and advantages of certain embodiments of the present disclosure will become more apparent from the following description in conjunction with the accompanying drawings, in which:
[0022] Figure 1 A simplified conceptual diagram illustrating a rechargeable lithium battery according to one or more embodiments of the present disclosure is illustrated.
[0023] Figures 2-5 Each is a schematic diagram illustrating a rechargeable lithium battery according to one or more embodiments of the present disclosure, in which Figure 2 A cylindrical battery is illustrated, Figure 3 A prismatic battery is illustrated, and Figure 4 and Figure 5 Each illustrates a pouch-type battery.
[0024] Figure 6 and Figure 7 Each illustrates a magnified view of a positive electrode active material layer of a rechargeable lithium battery according to one or more embodiments of the present disclosure.
[0025] Figure 8A A scanning electron microscope (SEM) image illustrating a positive electrode active material of Preparation Example 1-1 of the present disclosure is illustrated.
[0026] Figure 8B A scanning electron microscope (SEM) image illustrating a positive electrode active material of Preparation Example 1-2 of the present disclosure is illustrated.
[0027] Figure 9 A scanning electron microscope (SEM) image illustrating a positive electrode active material of Preparation Example 1-3 of the present disclosure is illustrated.
[0028] Figure 10 A scanning electron microscope (SEM) image illustrating a positive electrode active material of Preparation Example 1-4 of the present disclosure is illustrated. DETAILED DESCRIPTION
[0029] For a full understanding of the layout and effects of the present disclosure, one or more embodiments thereof will be described with reference to the accompanying drawings. It should be noted, however, that the present disclosure is not limited to the example embodiments described below and can be implemented in one or more suitable forms. Rather, the example embodiments are presented merely to illustrate the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.
[0030] In the present disclosure, it will be understood that if (for example, when) an element is referred to as being "on" another element, it can be directly on the other element or one or more intervening elements can be present therebetween. In contrast, if (for example, when) an element is referred to as being "directly on" another element, there are no intervening elements present. In the drawings, the size (e.g., thickness) of some components is exaggerated for effective explanation of the technical content. Throughout the present disclosure, the same reference numerals refer to the same elements, and a repeated description thereof is not provided for the sake of clarity.
[0031] Unless specifically stated otherwise in the present disclosure, the singular forms "a," "an," and "the" are intended to include plural forms, unless the context clearly indicates otherwise. Further, when describing embodiments of the present disclosure, the use of "may" indicates "one or more embodiments of the present disclosure." In addition, unless specifically stated otherwise, the phrases "A or B" or "A and / or B" can indicate "A but not B," "B but not A," and "both A and B." The terms "comprise(s) / comprising / comprises" and / or "include(s) / including / includes" used in the present disclosure do not exclude the presence of one or more other components.
[0032] As used herein, the term "combination thereof" can refer to a mixture, a stack, a composite, a copolymer, an alloy, a blend, or a reaction product of ingredients.
[0033] Unless specifically stated otherwise in the present description, the particle size / diameter can be an average particle size (average diameter) / average size. In addition, the particle size / diameter indicates an average particle size / average size (D 50 ) in which cumulative volume is about 50 vol% in a particle size distribution (e.g., a cumulative distribution). In other words, D 50 refers to an average diameter (or average size) of a particle at which cumulative volume corresponds to 50 vol% in a particle size distribution (e.g., a cumulative distribution), and refers to a value corresponding to a particle size of 50% from the smallest particle when the total number of particles is 100% in a distribution curve accumulated in order of the smallest particle size to the largest particle size. Further, D 90D90 refers to the average diameter (or average size) of particles in a particle size distribution (e.g., a cumulative distribution) where the cumulative volume corresponds to 90 vol% of the particles, and refers to the value corresponding to 90% of the particle size from the smallest particle when the total number of particles is 100% in a distribution curve that is accumulated in order of the smallest particle size to the largest particle size. 10 D10 refers to the average diameter (or average size) of particles in a particle size distribution (e.g., a cumulative distribution) where the cumulative volume corresponds to 10 vol% of the particles, and refers to the value corresponding to 10% of the particle size from the smallest particle when the total number of particles is 100% in a distribution curve that is accumulated in order of the smallest particle size to the largest particle size. The average particle diameter / average size (D 50 ) can be measured by methods widely applicable to those skilled in the art, for example, by a particle size analyzer (e.g., HORIBA, LA-950 laser particle size analyzer), a transmission electron microscope (TEM), or a scanning electron microscope (SEM). In one or more embodiments, a dynamic light scattering measurement device can be used for data analysis, counting the number of particles for each particle size range, and then based on the collected data, the average particle diameter / average size (D 50 ) value can be obtained by calculation. In one or more embodiments, a laser scattering method can be used to measure the average particle diameter / average size (D 50 ). In the laser scattering method, the target particles are dispersed in a dispersion solvent, introduced into a laser scattering particle diameter measurement device (e.g., MT3000 commercially available from Microtrac), irradiated with ultrasonic waves at about 28 kHz at a power of about 60 W, and then the average particle diameter / average size (D 50 ) is calculated in the measurement device at a standard particle size distribution of 50%. In the present disclosure, when the particles are spherical, the "diameter / size" indicates the average particle diameter, and when the particles are non-spherical, the "diameter / size" indicates the average long axis length of the particles.
[0034] Figure 1 is a simplified conceptual diagram of a rechargeable lithium battery according to one or more embodiments of the present disclosure. Referring to Figure 1 , the rechargeable lithium battery can include a positive electrode 10, a negative electrode 20, a separator 30, and an electrolyte (e.g., an electrolyte solution) ELL.
[0035] The positive electrode 10 and the negative electrode 20 can be spaced and / or separated (e.g., spaced apart and / or separated) from each other by the separator 30. The separator 30 can be disposed between the positive electrode 10 and the negative electrode 20. The positive electrode 10, the negative electrode 20, and the separator 30 can be in contact with the electrolyte solution ELL. For example, the positive electrode 10, the negative electrode 20, and the separator 30 can be immersed in the electrolyte solution ELL (e.g., impregnated with the electrolyte solution ELL).
[0036] The electrolyte solution ELL can be a medium for transporting lithium ions between the positive electrode 10 and the negative electrode 20. In the electrolyte solution ELL, lithium ions can move toward the positive electrode 10 or the negative electrode 20 through the separator 30.
[0037] The positive electrode 10
[0038] The positive electrode 10 for the rechargeable lithium battery can include a positive electrode current collector COL1 and a positive electrode active material layer AML1 formed on the positive electrode current collector COL1. The positive electrode active material layer AML1 can include a positive electrode active material (e.g., in the form of particles), and can further include a binder and / or a conductive material. Reference will be made to Figure 6 and Figure 7 The positive electrode active material layer AML1 according to one or more embodiments of the disclosure is described in more detail. In one or more embodiments, an aluminum (Al) foil can be used for the positive electrode current collector COL1, but embodiments of the disclosure are not limited thereto.
[0039] The negative electrode 20
[0040] The negative electrode 20 for the rechargeable lithium battery can include a negative electrode current collector COL2 and a negative electrode active material layer AML2 on the negative electrode current collector COL2. The negative electrode active material layer AML2 can include a negative electrode active material (e.g., in the form of particles), and can further include a binder and / or a conductive material (e.g., an electronically conductive material).
[0041] For example, in one or more embodiments, the negative electrode active material layer AML2 can include about 90 wt% to about 99.5 wt% of a negative electrode active material, about 0.5 wt% to about 5 wt% of a binder, and about 0 wt% to about 5 wt% of a conductive material, based on the total weight of the negative electrode active material layer of 100 wt%.
[0042] The binder can be used for the negative electrode active material particles to be well adhered to each other, and also for the negative electrode active material to be well adhered to the negative electrode current collector COL2. The binder can include a non-aqueous (e.g., water-insoluble) binder, an aqueous (water-soluble) binder, a dry binder, and / or a combination (e.g., any appropriate combination) thereof.
[0043] The non-aqueous binder can include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide imide, polyimide, and / or a combination (e.g., any appropriate combination) thereof.
[0044] The aqueous binder can be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluoro rubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenol resin, epoxy resin, polyvinyl alcohol, and / or a combination thereof (e.g., any suitable combination thereof).
[0045] When the aqueous binder is used as a binder in the negative electrode active material layer AML2, a cellulose-based compound capable of imparting viscosity can be further included. The cellulose-based compound can include at least one of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, and alkali metal salts thereof. The alkali metal can include sodium (Na), potassium (K), or lithium (Li).
[0046] The dry binder can be a polymer material capable of being fibrous. For example, the dry binder can be polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, and / or a combination thereof (e.g., any suitable combination thereof).
[0047] The conductive material can be used to impart electrical conductivity (e.g., electronic conductivity) to the electrode. Any material that does not cause chemical changes (e.g., does not cause undesirable chemical changes in the rechargeable lithium battery) and conducts electrons can be used in the battery. Non-limiting examples thereof can include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials including copper, nickel, aluminum, silver, etc. in the form of a metal powder or a metal fiber; conductive polymers such as polyphenylene derivatives; and / or a mixture thereof (e.g., any suitable mixture thereof).
[0048] The negative electrode current collector COL2 can include a copper foil, a nickel foil, a stainless steel foil, a titanium foil, a nickel foam, a copper foam, a polymer substrate coated with a conductive metal, and / or a combination thereof (e.g., any suitable combination thereof).
[0049] Negative electrode active material
[0050] The negative electrode active material can include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / de-doping lithium, or a transition metal oxide.
[0051] The material capable of reversibly intercalating / deintercalating lithium ions can include a carbon-based negative electrode active material such as, for example, crystalline carbon, amorphous carbon, and / or a combination thereof (e.g., any suitable combination thereof). The crystalline carbon can be graphite (such as, for example, amorphous (e.g., irregularly shaped), flaky, platelet-shaped, spherical, or fibrous natural graphite and / or artificial graphite). The amorphous carbon can be soft carbon, hard carbon, meso-phase pitch carbonization product, calcined coke, etc.
[0052] The lithium metal alloy includes lithium and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), silicon (Si), antimony (Sb), lead (Pb), indium (In), zinc (Zn), barium (Ba), radium (Ra), germanium (Ge), aluminum (Al), and tin (Sn).
[0053] The material capable of doping / de-doping lithium can be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material can include silicon, a silicon-carbon composite, SiO x (0 < x < 2), Si-Q alloys (where Q is selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and / or a combination thereof (e.g., any suitable combination thereof)), and / or a combination thereof (e.g., any suitable combination thereof). The Sn-based negative electrode active material can include Sn, SnO k (0 < k < 2) (e.g., Sn02), Sn-based alloys, and / or a combination thereof (e.g., any suitable combination thereof).
[0054] The silicon-carbon composite (e.g., in particulate form) can be a composite of silicon and amorphous carbon. According to one or more embodiments, the silicon-carbon composite can be in the form of silicon particles and amorphous carbon coating on the surface of each silicon particle. For example, in one or more embodiments, the silicon-carbon composite can include secondary particles (cores) in which primary silicon particles are assembled (agglomerated) and an amorphous carbon coating (shell) on the surface of the secondary particles. The amorphous carbon can also be between the primary silicon particles, and, for example, the primary silicon particles can each be coated with amorphous carbon. The secondary particles can be dispersed in an amorphous carbon matrix.
[0055] In one or more embodiments, the silicon-carbon composite can further include crystalline carbon. For example, the silicon-carbon composite can include a core including crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core.
[0056] In one or more embodiments, the Si-based negative electrode active material and / or the Sn-based negative electrode active material can be used in combination with a carbon-based negative electrode active material.
[0057] Separator 30
[0058] According to the type of the rechargeable lithium battery, a separator 30 can exist between the positive electrode 10 and the negative electrode 20. The separator 30 can include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, or a multilayer film of two or more layers thereof (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).
[0059] The separator 30 can include a porous substrate and a coating layer on a surface (e.g., one surface or both surfaces (e.g., two opposite surfaces)) of the porous substrate, the coating layer including an organic material, an inorganic material, and / or a combination (e.g., any suitable combination thereof) thereof.
[0060] The porous substrate can be a polymer film formed of any one polymer selected from the group consisting of polyolefins (such as polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyether ketones, polyarylether ketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene ethers, cyclic olefin copolymers, polyphenylene sulfides, polyethylene naphthalate, glass fibers, and polytetrafluoroethylene (e.g., Teflon), or a copolymer or mixture of two or more thereof.
[0061] The organic material can include a polyvinylidene fluoride-based polymer and / or a (meth)acrylic-based polymer.
[0062] The inorganic material can include inorganic particles selected from the group consisting of Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and / or a combination (e.g., any suitable combination thereof) thereof, but embodiments of the present disclosure are not limited thereto.
[0063] In one or more embodiments, the organic material and the inorganic material can be mixed in one coating layer, or a coating layer including the organic material and a coating layer including the inorganic material can be stacked.
[0064] Electrolyte solution ELL
[0065] The electrolyte solution ELL for the rechargeable lithium battery can include a non-aqueous organic solvent and a lithium salt.
[0066] The non-aqueous organic solvent can serve as a medium for transporting ions participating in electrochemical reactions of the battery.
[0067] The non-aqueous organic solvent can include a carbonate-based solvent, an ester-based solvent, an ether-based solvent, a ketone-based solvent, an alcohol-based solvent, an aprotic solvent, or a combination (e.g., any suitable combination thereof) thereof.
[0068] The carbonate-based solvent can include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), or the like.
[0069] The ester-based solvent can include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolide, methyl hydroxyvalerate, valerolactone, caprolactone, or the like.
[0070] The ether-based solvent can include dibutyl ether, tetraglyme, diglyme, glyme, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, or the like. In addition, the ketone-based solvent can include cyclohexanone, or the like. The alcohol-based solvent can include ethanol, isopropyl alcohol, or the like, and the aprotic solvent can include: nitriles (such as R-CN, where R is a C2 to C20 linear, branched, or cyclic hydrocarbon group, and can include a double bond, an aromatic ring, or an ether bond) or the like; amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane, or the like); sulfolane; or the like.
[0071] The non-aqueous organic solvent can be used alone or in combination of two or more.
[0072] In addition, if (for example, when) a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate can be mixed and used, and the cyclic carbonate and the chain carbonate can be mixed in a volume ratio of about 1:1 to about 1:9.
[0073] The lithium salt dissolved in the non-aqueous organic solvent supplies lithium ions to the rechargeable lithium battery, ensures the basic operation of the rechargeable lithium battery, and improves the transport and migration of lithium ions between the positive electrode and the negative electrode. The lithium salt can include at least one selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide, LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2)(where x and y are integers of 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluoro(oxalato)borate (LiDFOB), lithium difluorobis(oxalato)phosphate (LiDFBOP), and lithium bis(oxalato)borate (LiBOB).
[0074] The rechargeable lithium battery
[0075] Rechargeable lithium batteries can be classified into cylindrical, prismatic, pouch, or coin type batteries, etc. according to their shapes. Figures 2-5 Each is a schematic diagram illustrating a rechargeable lithium battery according to one or more embodiments of the present disclosure. Figure 2 A cylindrical battery is shown, Figure 3 A prismatic battery is shown, and Figure 4 A pouch battery is shown, and Figure 5 Each shows a pouch battery. Referring to Figures 2-5 A rechargeable lithium battery 100 can include an electrode assembly 40 including a separator 30 between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is included. The positive electrode 10, the negative electrode 20, and the separator 30 can be impregnated with an electrolyte solution. In some embodiments, as shown in Figure 2 A rechargeable lithium battery 100 can include a sealing member 60 that seals the case 50. In some embodiments, as shown in Figure 3 A rechargeable lithium battery 100 can include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. In some embodiments, as shown in Figure 4 and Figure 5 A rechargeable lithium battery 100 can include electrode tabs 70, which can be, for example, a positive electrode tab 71 and a negative electrode tab 72, serving as an electrical path for guiding the current generated in the electrode assembly 40 to the outside.
[0076] As non-limiting examples, rechargeable lithium batteries according to one or more embodiments can be applied to automobiles, mobile phones, and / or one or more appropriate types of electronic devices.
[0077] Figure 6 and Figure 7 Each illustrates a magnified view of a positive electrode active material layer of a rechargeable lithium battery according to one or more embodiments of the present disclosure. Referring to Figure 6 and Figure 7 As discussed above, the positive electrode active material layer AML1 (see Figure 1 ) can include first particles PTC1, second particles PTC2, third particles PTC3, a conductive material CDM (e.g., an electronic conductor), and a binder BND. The plurality of first particles PTC1, the plurality of second particles PTC2, and the plurality of third particles PTC3 can constitute a positive electrode active material according to one or more embodiments of the present disclosure.
[0078] In one or more embodiments, the positive electrode active material layer AML1 can further include a component serving as a sacrificial positive electrode.
[0079] In one or more embodiments, the content (e.g., amount) of the positive electrode active material particles (e.g., the plurality of first particles PTC1, the plurality of second particles PTC2, and the plurality of third particles PTC3) in the positive electrode active material layer AML1 can be about 90 wt% to about 99 wt% relative to 100 wt% of the total weight of the positive electrode active material layer AML1. Each of the contents of the binder BND and the conductive material (e.g., electronic conductor) CDM can be about 0.5 wt% to about 5 wt% relative to 100 wt% of the total weight of the positive electrode active material layer AML1.
[0080] The binder BND can bind the first particles PTC1, the second particles PTC2, the third particles PTC3, and the conductive material CDM to each other. For example, the binder BND can include at least one selected from the group consisting of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, an oxirane-containing polymer, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, and nylon, but embodiments of the present disclosure are not limited thereto.
[0081] The conductive material CDM can be used to improve the electrical conductivity (e.g., the electric conductivity) of the positive electrode active material layer AML1. Any conductive material that does not cause a chemical change in the positive electrode active material layer AML1 can be used as the conductive material CDM without limitation. For example, the conductive material CDM can include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials containing copper, nickel, aluminum, silver, etc. and having a form of a metal powder or a metal fiber (e.g., in the form of a metal powder or a metal fiber); conductive polymers such as polyphenylene derivatives; and / or a mixture (e.g., any appropriate mixture thereof) thereof.
[0082] Hereinafter, each of the first particles PTC1, the second particles PTC2, and the third particles PTC3 will be explained in more detail.
[0083] The first particles PTC1
[0084] The first particles PTC1 can include a lithium compound having an olivine structure represented by Chemical Formula 1.
[0085] Chemical Formula 1
[0086] Li a1 Fe x1 B 1 y1 PO 4-b1
[0087] In Chemical Formula 1, 0.8≤a1≤1.2, 0.95≤x1≤1.0, 0≤y1≤0.05, 0≤b1≤0.05, x1+y1=1, and B 1 may include (e.g., be) at least one element selected from the group consisting of Al, Ti, V, and Mg.B 1 may be a dopant doped in the first particle PTC1.
[0088] The dopant can have an effect of controlling the first primary particles of the first particle PTC1 to grow uniformly (e.g., substantially uniformly), thereby improving charging and discharging efficiency, low-temperature characteristics, and lifespan characteristics of the rechargeable lithium battery.
[0089] The first particle PTC1 has the advantages of high economic feasibility, high structural stability, and excellent or appropriate lifespan characteristics. Since Fe is included as a main component in the first particle PTC1, the first particle PTC1 is relatively inexpensive, and since the first particle PTC1 is structurally stable, chemical changes thereof can be relatively small even though repeated charging and discharging are performed.
[0090] In one or more embodiments, the first particle PTC1 can include a coating (e.g., a first coating) on a surface thereof. The coating can cover an entire surface (e.g., an entire outermost surface) of the first particle PTC1 or can cover a portion of the surface of the first particle PTC1. The first particle PTC1 includes a coating containing a carbon element. For example, the coating can include a carbon element and / or a carbon-containing compound. Due to the coating, the first particle PTC1 can have improved structural stability and electrical conductivity.
[0091] In one or more embodiments, the coating can further include at least one (e.g., at least one metal-containing compound) selected from the group consisting of an aluminum-containing compound, a titanium-containing compound, a magnesium-containing compound, and a vanadium-containing compound. The metal-containing compound (such as the aluminum-containing compound, the titanium-containing compound, the magnesium-containing compound, and the vanadium-containing compound) can be, for example, a metal oxide, a metal hydroxide, a metal carbonate, a synthetic compound thereof, and / or a mixture thereof (e.g., any appropriate mixture thereof). The metal-containing compound can further include other metal or non-metal elements. For example, in one or more embodiments, the metal-containing compound can further include lithium.
[0092] In one or more embodiments, the first particle PTC1 can further include carbon (a carbon element) derived from the coating. The content (e.g., amount) of carbon in the first particle PTC1 can be about 0.5 wt% to about 10 wt%, about 1 wt% to about 3 wt%, or about 1.5 wt% to about 2.5 wt% based on the total weight of the first particle PTC1 of 100 wt%.
[0093] The first particles PTC1 can each have a single particle form (e.g., in a single particle or monolithic particle form) and / or a secondary particle form (e.g., in a secondary particle form). For example, the first particles PTC1 can be present in only a single particle form, only a secondary particle form, or in a form in which single particles and secondary particles are mixed. Hereinafter, the first particles PTC1 in a single particle form (e.g., in a single particle or monolithic particle form) will be explained, and reference will be made to Figure 6 The first particles PTC1 in a single particle form (e.g., in a single particle or monolithic particle form) will be explained, and reference will be made to Figure 7 The first particles PTC1 in a secondary particle form (e.g., in a secondary particle form) will be explained.
[0094] In one or more embodiments, with reference to Figure 6 , the first particles PTC1 can have a single particle form (e.g., in a single particle or monolithic particle form). In the present disclosure, a single particle can refer to a separate particle having no internal grain boundary. A single particle has one morphology of a phase, and can refer to a separate particle, a monolithic structure, a whole structure, or a non-aggregated particle in which the particle exists as an un-aggregated independent phase. For example, in one or more embodiments, a single particle can be a single crystal. In one or more embodiments, a single particle can be a particle containing several crystals. In one or more embodiments, a single particle can be in a separate form. In one or more embodiments, a single particle can be in a form of 2 to 100 single particles attached to each other.
[0095] If (e.g., when) the first particles PTC1 are single particles, the first particles PTC1 can include at least one first primary particle. In one or more embodiments, the first particles PTC1 can have a spherical or spheroidal shape in which the first primary particles can be aggregated. In one or more embodiments, although the first primary particles are aggregated, the first particles PTC1 can not have a spherical shape, but can have a random shape.
[0096] If (e.g., when) the first particles PTC1 are single particles, the first particles PTC1 can be provided in one or more appropriate sizes. For example, in one or more embodiments, the average particle diameter of the first particles PTC1 can be about 0.5 micrometers (μm) to about 2.5 μm or about 1 μm. The minimum particle diameter of the first particles PTC1, i.e., the size of the first primary particles, can be about 100 nanometers (nm) to about 500 nm or about 200 nm to about 300 nm.
[0097] In one or more embodiments, the average particle diameter can be measured by a particle size analyzer. The average particle diameter (D 50 ) can refer to the diameter of a particle in which the cumulative volume of particles is about 50 vol% in a particle size distribution.
[0098] In one or more embodiments, the minimum particle size (i.e., the size of the first primary particles, e.g., the particle size of the smaller first particles PTC1, i.e., as used herein, the first particles PTC1 refer to single particles whose size corresponds to the minimum particle size) can refer to the average diameter measured by randomly selecting about 30 primary particles in an electron microscope image of the first particles PTC1.
[0099] If (e.g., when) the first particles PTC1 are single particles, the porosity of the first particles PTC1 can be less than about 30%. Here, the porosity (n) can be defined as the pore volume (Vp) divided by the total volume of the particles (Vt), or
[0100]
[0101] The span value of the first particles PTC1 analyzed by the particle size analyzer can range from about 0.3 to about 0.75. As used herein, the terms “D 10 ” “D 50 ” and “D 90 ” each refer to the average particle size exhibited by about 10%, 50%, or 90% of the cumulative volume of the particles in the particle size distribution, respectively. In particle size analysis, the span value is a value that indicates the width of the particle size distribution, or
[0102]
[0103] A lower span value indicates a more uniform particle size distribution, meaning that the particles are more consistent in size. Conversely, a higher span value indicates a wider range of particle sizes in the sample.
[0104] In one or more embodiments, referring again to Figure 7 , the first particles PTC1 can be in the form of (e.g., be in the form of) secondary particles. The secondary particles can be in the form of agglomerates and refer to a form in which two or more first primary particles are aggregated. For example, one first particle PTC1 can include a plurality of first primary particles aggregated with each other. The first particles PTC1 can have a spherical or spheroid shape.
[0105] In one or more embodiments, if (e.g., when) the first particulate PTC1 is in the form of a secondary particulate (i.e., is in the form of a secondary particulate), the first particulate PTC1 can further include a grain boundary coating on the surface of each first primary particulate. The grain boundary coating can be present in the first particulate PTC1. The grain boundary coating can be formed along the interface between the first primary particulates inside the first particulate PTC1. For example, the grain boundary coating can refer to a layer formed by a material coated on the grain boundaries in the first particulate PTC1. The grain boundary coating can include elemental carbon and / or a carbon-containing compound. The grain boundary coating can further include at least one metal-containing compound selected from the group consisting of an aluminum-containing compound, a titanium-containing compound, a magnesium-containing compound, and a vanadium-containing compound.
[0106] If (e.g., when) the first particulate PTC1 is a secondary particulate, the interior of the above-described first particulate PTC1 can refer to the entire interior of the first particulate PTC1 except for the surface (e.g., the outermost surface) of the first particulate PTC1. For example, the interior of the first particulate PTC1 can refer to the entire interior from about 10 nm in depth from the surface (e.g., the outermost surface) of the first particulate PTC1 to the center of the first particulate PTC1, or from about 10 nm in depth from the surface of the first particulate PTC1 to a region of about 2 μm in depth from the surface of the first particulate PTC1.
[0107] If (e.g., when) the first particulate PTC1 is a secondary particulate, because the first particulate PTC1 can further include a grain boundary coating portion (i.e., a grain boundary coating), the structural stability thereof can be enhanced, and a substantially uniform coating layer can be formed on the surface of the first particulate PTC1. In other words, the grain boundary coating portion / grain boundary coating can facilitate the formation of a substantially uniform coating layer on the surface of the first particulate PTC1. In addition, because the first particulate PTC1 further includes the grain boundary coating portion / grain boundary coating, the electrical conductivity of the first particulate PTC1 can be further improved.
[0108] If (e.g., when) the first particulate PTC1 is a secondary particulate, the first particulate PTC1 can further include carbon derived from the coating and / or the grain boundary coating. The content (e.g., amount) of carbon elements in the first particulate PTC1 can be about 0.5 wt% to about 10 wt%, about 1 wt% to about 3 wt%, or about 1.5 wt% to about 2.5 wt%, based on the total weight of 100 wt% of the first particulate PTC1. If (e.g., when) the first particulate PTC1 is a secondary particulate, the content (e.g., amount) of carbon can be greater than in embodiments in which the first particulate PTC1 is a single particulate.
[0109] If (for example, when) the first particles PTC1 are secondary particles, the average particle size of the first particles PTC1 can be about 2 μm to about 15 μm, about 3 μm to about 10 μm, or about 3 μm to about 7 μm. For example, in one or more embodiments, the average particle size of the first particles PTC1 can be about 5 μm. In one or more embodiments, the average particle size can be measured using a particle size analyzer. The average particle size (D 50 ) can refer to the diameter of particles whose cumulative volume is about 50 vol% in the particle size distribution.
[0110] If (for example, when) the first particles PTC1 are secondary particles, the average size of the first primary particles can be less than about 200 nm. For example, in one or more embodiments, the average size of the first primary particles can be about 10 nm to about 200 nm, about 20 nm to about 200 nm, about 50 nm to about 200 nm, or about 100 nm to about 200 nm. In one or more embodiments, the average particle size (average size) of the first primary particles can refer to the average diameter measured by randomly selecting about 30 primary particles in an electron microscope image of the positive electrode active material. The size of the first primary particles can be substantially uniform.
[0111] If (for example, when) the first particles PTC1 are in the form of secondary particles, the size of the first primary particles can be smaller than in embodiments in which the first particles PTC1 are single particles. For example, the size of the first primary particles in embodiments in which the first particles PTC1 are in the form of secondary particles can be about 100 nm smaller than the size of the first primary particles in embodiments in which the first particles PTC1 are in the form of single particles.
[0112] If (for example, when) the first particles PTC1 are secondary particles, the average particle size of the first particles PTC1 and the average size of the first primary particles satisfy the ranges described above, and if (for example, when) the size of the first primary particles is substantially uniform, the charge and discharge capacity of the rechargeable lithium battery including the first particles PTC1 and the capacity at low temperatures can be improved.
[0113] If (for example, when) the first particles PTC1 are secondary particles, the porosity of the first particles PTC1 can be about 20% to about 40%. The span value of the first particles PTC1 analyzed by the particle size analyzer can be about 0.3 to about 0.75.
[0114] If (for example, when) the first particles PTC1 are secondary particles, the positive electrode active material layer AML1 (see Figure 1 ) can be smoothly adhered to the positive electrode current collector COL1 (see Figure 1For example, the content (e.g., amount) of the binder BND can be about 0.5 wt% to about 3 wt% based on the total weight of the positive electrode active material layer AML1. This can increase due to the interaction between the first particles PTC1 and the positive electrode current collector COL1 (see Figure 1 If (for example, when) the content (e.g., amount) of the binder BND contained in the positive electrode active material layer AML1 is reduced, the content (e.g., amount) of the positive electrode active material can be correspondingly increased, thereby achieving the effect of improving the capacity and energy density of the battery. In addition, by reducing the content (e.g., amount) of the binder, thereby reducing the resistance, the effect of improving the electrical conductivity of the positive electrode can be achieved.
[0115] In the context of the present disclosure, unless otherwise defined, the first particles PTC1 can exist in two forms: single particles and secondary particles. Single particles are individual, non-aggregated particles that can be single crystals or contain several crystals. These particles have a uniform structure without internal grain boundaries, which contributes to their high structural stability and minimal chemical changes during repeated charging and discharging. Single particles generally have a small average particle size ranging from about 0.5 microns to about 2.5 microns, and single particles are provided in various sizes, enhancing the charging and discharging efficiency, low-temperature characteristics, and life characteristics of the rechargeable lithium battery. On the other hand, secondary particles are aggregates of multiple first primary particles, forming a polycrystalline structure. These secondary particles can include a grain boundary coating that improves structural stability and electrical conductivity. Secondary particles have a larger average particle size ranging from about 2 microns to about 15 microns, and secondary particles can have a higher carbon content derived from the coating. The secondary particle form allows for easier adhesion to the positive electrode current collector with less binder, increasing the positive electrode active material content and improving the capacity and energy density of the battery. The porosity and particle size distribution of the secondary particles also contribute to enhancing battery performance.
[0116] The second particles PTC2
[0117] The second particles PTC2 can include a lithium compound having a spinel structure represented by Chemical Formula 2.
[0118] Chemical Formula 2
[0119] Li a2 Mn x2 C 1 y2 O 4-b2
[0120] In Chemical Formula 2, 0.8 ≤ a2 ≤ 1.2, 1.9 ≤ x2 ≤ 2.05, 0 ≤ y2 ≤ 0.05, 0 ≤ b2 ≤ 0.05, and C 1may include (e.g., be) at least one element selected from the group consisting of Al and Mg.C 1 may be a dopant doped in the second particle PTC2. In one or more embodiments, in Chemical Formula 2, 0.8 < a2≤ 1.2, 1.95 ≤ x2≤ 2.05, 0 ≤ y2≤ 0.05, 0 ≤ b2≤ 0.05, 2 ≤ x2+y2≤ 2.1 can be satisfied. In one or more embodiments, in Chemical Formula 2, 0.8 < a2≤ 1.2, 1.95 ≤ x2≤ 2, 0 ≤ y2≤ 0.05, 0 ≤ b2≤ 0.05, x2+y2= 2 can be satisfied.
[0121] The dopant can have an effect of controlling the second primary particles of the second particle PTC2 to grow uniformly (e.g., substantially uniformly), thereby improving the charge and discharge efficiency, low-temperature characteristics, and life characteristics of the rechargeable lithium battery.
[0122] The second particle (PTC2) has the advantages of high output characteristics, high average voltage, and excellent or proper structural stability. The second particle PTC2 can have a spinel structure composed of a lattice structure of tetrahedrons and octahedrons. Since the lattice structure has one or more proper channels, lithium ions can be smoothly intercalated / deintercalated, thereby producing excellent or proper output characteristics. Due to Mn in the second particle PTC2, the lattice structure can be more stable. Due to the structural stability, the electrochemical characteristics of the particle can be maintained even at a high voltage, allowing operation at a high voltage.
[0123] The second particle PTC2 is a lithium manganese oxide, and can be a positive electrode active material in which cobalt in a lithium cobalt oxide is substituted with manganese. In one or more embodiments of the present disclosure, the cobalt (Co) content (e.g., amount) of the second particle PTC2 can be very small, substantially equivalent to being omitted or not present. For example, in one or more embodiments, the cobalt (Co) content (e.g., amount) of the second particle PTC2 can be about 100 ppm or less. Substantial omission of cobalt (Co) in the positive electrode active material according to the present disclosure, and can provide an economical rechargeable lithium battery with high capacity and operating voltage.
[0124] Referring again to Figure 6 and Figure 7 In one or more embodiments, the second particle PTC2 can have a polycrystalline form, and can include a secondary particle in which two or more second primary particles are aggregated. For example, one second particle PTC2 can include a plurality of second primary particles aggregated with each other. In one or more embodiments, the second particle PTC2 can have an aggregated spherical shape of the second primary particles, and although the second primary particles are aggregated, the second particle PTC2 can have a random shape in some embodiments.
[0125] The average particle size of the second particles PTC2 can be about 3 μm to about 20 μm, about 4 μm to about 15 μm, or about 5 μm to about 10 μm. For example, in one or more embodiments, the average particle size of the second particles PTC2 can be about 8 μm. In one or more embodiments, the average particle size can be measured by a particle size analyzer. The average particle size (D 50 ) can refer to the diameter of particles whose cumulative volume is about 50 vol% in the particle size distribution.
[0126] The average size of the second primary particles constituting the second particles PTC2 can be about 3 μm or less. For example, in one or more embodiments, the average size of the second primary particles can be about 300 nm to about 3 μm, about 0.5 μm to about 3 μm, about 1 μm to about 3 μm, or about 2 μm to about 3 μm. In one or more embodiments, the average size of the second primary particles can refer to the average diameter / size by randomly selecting about 30 primary particles in an electron microscope image for the positive electrode active material. The size of the second primary particles can be substantially uniform. The average size of the second primary particles can be greater than the average size of the first primary particles. The difference between the average size of the second primary particles and the average size of the first primary particles can be about 300 nm or greater.
[0127] In one or more embodiments, the second particles PTC2 can include a second coating layer on the surface thereof. By including the second coating layer, collapse of the structure of the second particles PTC2 due to repeated charging and discharging can be effectively suppressed or reduced.
[0128] The second coating layer can include a metal-containing compound selected from an aluminum-containing compound, a magnesium-containing compound, and / or a combination (e.g., any suitable combination thereof). The metal-containing compound in the second coating layer can be, for example, a metal oxide, a metal hydroxide, a metal carbonate, a synthetic compound thereof, and / or a mixture (e.g., any suitable mixture thereof). The metal-containing compound can further include other metal or non-metal elements. For example, in one or more embodiments, the second coating layer can further include lithium, manganese, and / or nickel.
[0129] In one or more embodiments, a method for measuring the metal content (e.g., amount) in the second coating layer of the second particles PTC2 can include scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS) on the second particles PTC2. Through the analysis, the aluminum and / or magnesium content in the second coating layer can be confirmed. In one or more embodiments, as a method for measuring the metal content (e.g., amount) in the second coating layer, in addition to SEM-EDS, inductively coupled plasma mass spectrometry (ICP-MS), inductively coupled plasma optical emission spectroscopy (ICP-OES), etc. can be used.
[0130] Third particles PTC3
[0131] The third particle PTC3 can include a lithium compound represented by Chemical Formula 3.
[0132] Chemical Formula 3
[0133] Li a3 Co x3 D 1 y3 O 4-b3
[0134] In Chemical Formula 3, 5.9 < a3 ≤ 6.1, 0.9 ≤ x3 ≤ 1.05, 0 ≤ y3 ≤ 0.05, and 0 ≤ b3 ≤ 0.05. D 1 may include (e.g., be) at least one element selected from the group consisting of Al and Mg. The dopant can improve the surface stability and structural stability of the third particle PTC3. In one or more embodiments, in Chemical Formula 3, 5.9 < a3 ≤ 6.1, 0.95 ≤ x3 ≤ 1, 0 ≤ y3 ≤ 0.05, 0 ≤ b3 ≤ 0.05, and x3 + y3 = 1 can be satisfied.
[0135] The third particle PTC3 has the advantage of high capacity energy density.
[0136] In one or more embodiments, with reference to Figure 6 The third particle PTC3 can have a single particle form (e.g., in a single particle or monolithic particle form). In the present disclosure, a single particle can refer to a separate particle having no grain boundary inside. A single particle has one morphology phase, and can refer to a separate particle, a monolithic structure, a whole structure, or a non-aggregated particle in which the particle exists as an un-aggregated independent phase. For example, in one or more embodiments, a single particle can be a single crystal. In one or more embodiments, a single particle can be a particle containing several crystals. In one or more embodiments, a single particle can be in a separate form. In one or more embodiments, a single particle can be in a form of 2 to 100 single particles attached to each other.
[0137] If (e.g., when) the third particle PTC3 is a single particle, the third particle PTC3 can include at least one third primary particle. In one or more embodiments, the third particle PTC3 can have a spherical or ellipsoidal shape in which the third primary particles can be aggregated. In one or more embodiments, although the third primary particles are aggregated, the third particle PTC3 can not have a spherical shape, but can have a random shape.
[0138] Figure 6 and Figure 7Illustrated is an embodiment in which the third particles PTC3 are in a form comprising only one particle, although the third particles PTC3 can have a spherical or ellipsoidal shape in which two or more third primary particles are aggregated, or a random shape. For example, in one or more embodiments, the third particles PTC3 can have a random form in which third primary particles are aggregated, as shown in FIG. 3B. With reference to FIG. 3B, the aggregated shape of the third primary particles can be relatively more irregular than the aggregated shapes of the first and second primary particles described above. Figure 10 Figures 8B-10 With reference to FIG. 3B, the aggregated shape of the third primary particles can be relatively more irregular than the aggregated shapes of the first and second primary particles described above.
[0139] If (for example, when) the third particles PTC3 are single particles, the third particles PTC3 can be provided in one or more suitable sizes. For example, in one or more embodiments, the average particle size of the third particles PTC3 can be from about 2 μιη to about 8 μιη. The minimum particle size of the third particles PTC3 (i.e., the size of the third primary particles) can be from about 100 nm to about 500 nm. The average particle size of the third particles PTC3 can be greater than the average particle size of the first particles PTC1 described above. If (for example, when) the third particles PTC3 comprise a plurality of single particles (e.g., a plurality of third primary particles), the average size of the third primary particles of the third particles PTC3 can be greater than the average size of the first primary particles.
[0140] In one or more embodiments, the third particles PTC3 can include a third coating on the surface thereof. The coating can function to inhibit or reduce the structural collapse of the third particles PTC3 during repeated charging and discharging.
[0141] The third coating can include a metal-containing compound selected from the group consisting of an aluminum-containing compound, a magnesium-containing compound, and / or combinations thereof (e.g., any suitable combination thereof). The metal-containing compound in the third coating can be, for example, a metal oxide, a metal hydroxide, a metal carbonate, a synthetic compound thereof, and / or a mixture thereof (e.g., any suitable mixture thereof). The metal-containing compound can further include other metal or non-metal elements. For example, in one or more embodiments, the third coating can further include lithium, manganese, and / or nickel.
[0142] Li from the third particles PTC3 can act as an irreversible Li that moves to the negative electrode during initial charging but does not return to the positive electrode during discharging. For example, the third particles PTC3 can act as a sacrificial positive electrode. In one or more embodiments, the third particles PTC3 can act to supply Li in a formation process as a first charging and discharging stage, and can not participate in subsequent charging and discharging processes, e.g., the third particles PTC3 can be electrochemically deactivated after the first cycle.
[0143] In the formation process, the third particles PTC3 can participate in forming a solid electrolyte interface (SEI) film on the surface of the negative electrode. Li derived from the third particles PTC3 can be converted into irreversible Li, which then no longer participates in the charge and discharge reactions.
[0144] The third particles PTC3 have a high capacity and energy density characteristic, and the amount of irreversible Li supplied during initial charging and discharging can be sufficient. The third particles PTC3 are sacrificed, such that Li derived from a main active material (to be explained later) is not combined with the irreversible Li, and the capacity of the main active material (to be explained later) can be realized as an amount initially designed, and ultimately, an effect of increasing the capacity and energy density of the rechargeable lithium battery can be shown. The positive electrode active material according to the present disclosure includes an appropriate or suitable amount of the third particles PTC3, and can increase the capacity and energy density of the rechargeable lithium battery.
[0145] The third particles PTC3 according to one or more embodiments of the present disclosure can include Li6CoO4. Li6CoO4 can provide a large amount (e.g., a suitable amount) of Li atoms in the formation process, and can provide more irreversible Li. Accordingly, an effect of being a sacrificial positive electrode can be obtained to a greater extent. For example, Li6CoO4 can be decomposed to provide six Li atoms between about 3.0 V and about 4.0 V. However, Li6CoO4 is merely an example, and embodiments of the present disclosure are not limited thereto.
[0146] If (e.g., when) the content (e.g., amount) of the third particles PTC3 contained in the positive electrode active material is within a certain content (e.g., amount) range, the third particles PTC3 can play a role of compensating for the irreversible Li without affecting the battery characteristics targeted when the main active material (to be explained later) is designed. The content (e.g., amount) range of the third particles PTC3 will be explained later in more detail.
[0147] Main Active Material
[0148] Reference Figure 6 and Figure 7 The main active material according to one or more embodiments of the present disclosure will be explained in more detail below.
[0149] The first particles PTC1 and the second particles PTC2 can constitute the main active material (main component). The content (e.g., amount) of the main active material can be about 95 parts by weight to about 99.5 parts by weight, based on about 100 parts by weight of the positive electrode active material.
[0150] Compared to other positive electrode active materials, the lithium iron phosphate-based positive electrode active material (first particles PTC1) having an olivine crystal structure can have the advantage of being relatively inexpensive and having a stable structure and superior or appropriate lifespan characteristics. The lithium manganese oxide-based positive electrode active material (second particles PTC2) having a spinel structure can have the advantage of having a high average voltage. Since the first particles PTC1 and the second particles PTC2 are mixed and used as a main active material in the positive electrode active material according to the disclosure, the advantages of both the first particles PTC1 and the second particles PTC2 can be obtained at the same time. For example, the properties of being inexpensive and having superior or appropriate lifespan characteristics, while operating at a high operating voltage, can be achieved.
[0151] The mixing ratio of the first particles PTC1 and the second particles PTC2 can be about 40:60 to about 90:10, about 46:54 to about 37:63, or about 55:45 to about 37:63, based on weight. In the main active material consisting of the first particles PTC1 and the second particles PTC2, the Mn content (e.g., amount) with respect to the metal elements other than lithium (e.g., total metal elements) can be about 40 mol% to about 75 mol% or about 50 mol% to about 70 mol%. The Mn content (e.g., amount) can be similar to that of a conventional lithium manganese iron phosphate positive electrode active material (hereinafter, referred to as LMFP).
[0152] By suitably or appropriately mixing the first particles PTC1 and the second particles PTC2 to satisfy the Mn content (e.g., amount) range, the positive electrode active material according to the disclosure can be easily manufactured / prepared and processed, which exhibits similar electrochemical characteristics to those of LMFP. Since LMFP operates at a high average voltage, it can be an alternative solution to alleviate the defect of the low average voltage of the lithium iron phosphate-based positive electrode active material (hereinafter, referred to as LFP). However, LMFP can have limitations because it is difficult to manufacture and process if (e.g., when) applied to an actual process. By controlling the Mn content (e.g., amount) of the main active material using the second particles PTC2, the positive electrode active material according to the disclosure can be easily manufactured and processed, while exhibiting similar characteristics to those of LMFP.
[0153] Positive electrode active material
[0154] Reference Figure 6 and Figure 7 The positive electrode active material according to one or more embodiments of the disclosure will be explained in more detail herein.
[0155] The positive electrode active material according to the disclosure can include the first particles PTC1, the second particles PTC2, and the third particles PTC3.
[0156] Compared with other positive electrode active materials, the first and second PTC particles 1 and 2 have the disadvantage of relatively low energy density. In addition to the first and second PTC particles 1 and 2, the positive electrode active material according to the present disclosure can have high capacity and energy density by further including the third PTC particle 3 that can serve as a sacrificial positive electrode.
[0157] Based on about 100 parts by weight of the positive electrode active material, the content (e.g., amount) of the third particle PTC3 may be about 0.5 parts by weight to about 5 parts by weight or about 0.5 parts by weight to about 1 part by weight. If (e.g., when) the content (e.g., amount) of the third particle PTC3 satisfies the above range (time), the effect of compensating for irreversible Li can be achieved without affecting the desired or appropriate battery characteristics when designing the main active material. For example, if (e.g., when) the content (e.g., amount) of the third particle PTC3 satisfies the above range (time), the capacity and energy density characteristics can be improved while minimizing or reducing the reduction in the life and stability of the positive electrode active material.
[0158] The content (e.g., amount) of the third particle PTC3 in the positive electrode active material can be determined within a range in which the charge and discharge efficiency of the positive electrode is not lower than the charge and discharge efficiency of the negative electrode. If the charge and discharge efficiency of the positive electrode is higher than that of the negative electrode, the excess efficiency may not be used and may be wasted. The charge and discharge efficiency refers to the initial discharge amount compared to the initial charge amount. For example, the charge and discharge efficiency of a graphite negative electrode may be about 90% or about 91.5%, and the charge and discharge efficiency of the positive electrode may be about 95%. In this case, the positive electrode active material may further include the third particle PTC3 so that the charge and discharge efficiency of the positive electrode is not lower than about 90% or about 91.5%. By considering the above range, the energy density characteristics can be improved without sacrificing the life characteristics.
[0159] According to the positive electrode active material of the present disclosure, the powder compaction density (PD) may be high. In one or more embodiments, the powder compaction density of the positive electrode active material of the present disclosure may be about 2 g / cc to about 5 g / cc or about 2.5 g / cc to about 4 g / cc or about 2.5 g / cc to about 3.0 g / cc. This may be higher than the powder compaction density of ordinary LFP. High powder compaction density can help improve the life characteristics of rechargeable lithium batteries and increase energy density. The uniform and dense distribution of electrode active materials (e.g., positive electrode active materials) can help maintain the consistency of electrochemical reactions during charging and discharging processes, which can help improve life characteristics. Because more electrode active materials (e.g., positive electrode active materials) are stored in a limited space, and more energy can be stored per unit volume, it helps to increase energy density.
[0160] A rechargeable lithium battery including a positive electrode active material according to one or more embodiments of the present disclosure can have a high average voltage. In one or more embodiments, the average voltage of the rechargeable lithium battery of the present disclosure can be about 3 V to about 4 V. In one or more embodiments, the average voltage range of the present disclosure can be about 3.5 V to about 3.7 V, which can be higher than the average voltage of ordinary LFP. Because the energy density is proportional to the average voltage, the above average voltage can help to increase the energy density. In the present disclosure, the term "average voltage" can refer to the average voltage of a fully charged rechargeable lithium battery.
[0161] A rechargeable lithium battery including a positive electrode active material according to one or more embodiments of the present disclosure can have a high energy density. In one or more embodiments, the energy density of the rechargeable lithium battery of the present disclosure can be about 300 Wh / kg to about 600 Wh / kg, about 400 Wh / kg to about 500 Wh / kg, or about 430 Wh / kg to about 480 Wh / kg.
[0162] A rechargeable lithium battery including a positive electrode active material according to one or more embodiments of the present disclosure can have a high lifespan characteristic. In one or more embodiments, the rechargeable lithium battery of the present disclosure can have a capacity retention rate of about 95% or more after 50 charge and discharge cycles under specific current and voltage conditions. In one or more embodiments, if (for example, when) the initial charge is performed under constant current (about 0.2 C) and constant voltage (about 4.25 V) conditions, the initial discharge is performed under constant current (about 0.2 C) conditions to about 2.5 V, and then the charge and discharge are performed 50 times (when) at about 0.2 C / 0.2 C, the capacity retention rate can be about 95% to about 100% or about 98% to about 100%, which can be higher than the lifespan characteristic of ordinary LFP.
[0163] Hereinafter, examples, comparative examples, and reference examples of the present disclosure will be described. However, the examples are for the illustration of the present disclosure only, and the present disclosure is not limited to the examples.
[0164] Preparation Example 1-1: Preparation of first particles having a single particle form
[0165] FePO4 iron phosphate precursor, lithium carbonate, and titanium dioxide were mixed in a molar ratio of Fe:Li:Ti = about 1 : 1.03:0.004. To the mixture was added 10 wt% of glucose based on the total weight of the FePO4 iron phosphate precursor, lithium carbonate, and titanium dioxide. The mixture was subjected to a wet milling process by ball milling. The mixture was evaporated and dried in a heated pan and placed in a vacuum oven for about 4 hours at about 120 °C. The dried mixture was then baked under a nitrogen atmosphere for about 10 hours at about 750 °C. The baked product was milled to obtain first particles in a single particle form (e.g., in the form of single particles). The average size of the first primary particles in the first particles in a single particle form was about 200 nm to about 300 nm.
[0166] Preparation Example 1-2: Preparation of first particles in a secondary particle form
[0167] FePO4 iron phosphate precursor, lithium carbonate, and titanium dioxide were mixed in a molar ratio of Fe:Li:Ti = about 1 : 1.03:0.004. To the mixture was added 10 wt% of glucose based on the total weight of the FePO4 iron phosphate precursor, lithium carbonate, and titanium dioxide. The mixture was subjected to a wet milling process by ball milling. The mixture was evaporated and dried in a heated pan and placed in a vacuum oven for about 4 hours at about 120 °C. The dried mixture was then baked under a nitrogen atmosphere for about 10 hours at about 750 °C. The baked product was milled to obtain first particles in a single particle form (e.g., in the form of single particles). The average size of the first primary particles in the first particles in a single particle form was about 200 nm to about 300 nm.
[0168] In other words, Preparation Example 1-1 describes a process to produce first particles in a single particle form. It includes mixing FePO4 iron phosphate precursor, lithium carbonate, and titanium dioxide in a specific molar ratio, adding glucose, and wet milling. The mixture is then dried, baked under a nitrogen atmosphere, and milled to produce single particles with an average size of 200 nm to 300 nm. Preparation Example 1-2 outlines a method for preparing first particles in a secondary particle form. The same initial materials and molar ratio are used, but the mixture is dried by spray drying under specific conditions before baking. This process produces first particles in a secondary particle form with first primary particles having an average size of 100 nm to 200 nm.
[0169] Preparation Example 1-3: Preparation of second particles
[0170] Li2CO3 and the thus-synthesized MnO2 were mixed so that the molar ratio of Li and Mn became about 1 :2, and heated at about 600°C for about 10 hours, to synthesize LiMn2O4 particles having an average particle diameter of about 7 μm.
[0171] Li2CO3 and the thus-synthesized MnO2 were mixed so that the molar ratio of Li and Mn became about 1 :2, and heated at about 600°C for about 10 hours, to synthesize LiMn2O4 particles having an average particle diameter of about 7 μm.
[0172] Preparation Example 1-4: Preparation of Third Particles
[0173] LiO and CoO were mixed in a molar ratio of about 6: 1. The mixed powder was calcined at about 600°C for about 24 hours under a nitrogen atmosphere. Then, the resultant was naturally cooled. The cooled powder was ground using an air jet mill at about 6000 rpm to obtain third particles. The chemical formula of the third particles was Li6CoO4.
[0174] Preparation Example 2-1: Preparation of Primary Active Material
[0175] The primary active material was prepared by mixing the first particles (single particle form) of Preparation Example 1-1 and the second particles of Preparation Example 1-3 in a weight ratio of about 46:54. In this case, the Mn content (e.g., amount) with respect to the metal elements other than lithium in the primary active material was about 60 mol%.
[0176] Preparation Example 2-2
[0177] The primary active material was prepared by mixing the first particles (single particle form) of Preparation Example 1-1 and the second particles of Preparation Example 1-3 in a weight ratio of about 55:45. In this case, the Mn content (e.g., amount) with respect to the metal elements other than lithium in the primary active material was about 50 mol%.
[0178] Preparation Example 2-3
[0179] The primary active material was prepared by mixing the first particles (secondary particle form) of Preparation Example 1-2 and the second particles of Preparation Example 1-3 in a weight ratio of about 46:54. In this case, the Mn content (e.g., amount) with respect to the metal elements other than lithium in the primary active material was about 60 mol%.
[0180] Preparation Example 2-4
[0181] The primary active material was prepared by mixing the first particles (in the form of secondary particles) of Preparation Example 1-2 and the second particles of Preparation Example 1-3 in a weight ratio of about 55:45. In this case, the Mn content (e.g., amount) with respect to the metal elements other than lithium in the primary active material was about 50 mol%.
[0182] Comparative Example 1
[0183] The primary active material was prepared by mixing the first particles (in the form of secondary particles) of Preparation Example 1-2 and the second particles of Preparation Example 1-3 in a weight ratio of about 59:41. In this case, the Mn content (e.g., amount) with respect to the metal elements other than lithium in the primary active material was about 45 mol%.
[0184] Comparative Example 2
[0185] The primary active material was prepared by mixing the first particles (in the form of secondary particles) of Preparation Example 1-2 and the second particles of Preparation Example 1-3 in a weight ratio of about 32:68. In this case, the Mn content (e.g., amount) with respect to the metal elements other than lithium in the primary active material was about 75 mol%.
[0186] Example 1: Preparation of Final Positive Electrode Active Material
[0187] The primary active material was prepared by mixing the primary active material of Preparation Example 2-2 and the third particles of Preparation Example 1-4 in a weight ratio of about 99.5:0.5. The weight ratio of the first particles (single particles): the second particles: the third particles was about 54.7:44.8:0.5.
[0188] Example 2
[0189] The primary active material was prepared by mixing the primary active material of Preparation Example 2-2 and the third particles of Preparation Example 1-4 in a weight ratio of about 99:1. The weight ratio of the first particles (single particles): the second particles: the third particles was about 54.5:44.6:1.0.
[0190] Example 3
[0191] The primary active material was prepared by mixing the primary active material of Preparation Example 2-4 and the third particles of Preparation Example 1-4 in a weight ratio of about 99.5:0.5. The weight ratio of the first particles (secondary particles): the second particles: the third particles was about 54.7:44.8:0.5.
[0192] Example 4
[0193] The primary active material was prepared by mixing the primary active material of Preparation Example 2-4 and the third particles of Preparation Example 1-4 in a weight ratio of about 99:1. The weight ratio of the first particles (secondary particles) : the second particles : the third particles was about 54.5:44.6:1.0.
[0194] Reference Example 3
[0195] The primary active material was prepared by mixing the primary active material of Preparation Example 2-2 and the third particles of Preparation Example 1-4 in a weight ratio of about 98.5:1.5. The weight ratio of the first particles (single particles) : the second particles : the third particles was about 54.2:44.3:1.5.
[0196] Reference Example 4
[0197] The primary active material was prepared by mixing the primary active material of Preparation Example 2-4 and the third particles of Preparation Example 1-4 in a weight ratio of about 98.5:1.5. The weight ratio of the first particles (secondary particles) : the second particles : the third particles was about 54.2:44.3:1.5.
[0198] Manufacture of positive electrode
[0199] A positive electrode active material slurry was prepared by mixing 95 wt% of the final positive electrode active material, 3 wt% of a polyvinylidene fluoride binder, and 2 wt% of a carbon black conductive material in an N-methylpyrrolidone solvent. The positive electrode active material slurry was coated on an aluminum current collector, dried and roll-pressed to manufacture a positive electrode.
[0200] Manufacture of negative electrode
[0201] A negative electrode active material slurry was prepared by mixing the Si-graphite composite, a binder, and a conductive material in an N-methylpyrrolidone solvent. The negative electrode active material slurry was coated on a copper current collector, dried and roll-pressed to manufacture a negative electrode.
[0202] Manufacture of rechargeable lithium battery
[0203] A 2032 type (kind) coin half-cell was formed using the prepared positive electrode and a lithium metal counter electrode as a counter electrode. A separator (thickness: about 16 μm) composed of a porous polyethylene (PE) film was disposed between the positive electrode and the lithium metal counter electrode, and an electrolyte solution was injected to manufacture a rechargeable lithium battery. As the electrolyte solution, an electrolyte solution obtained by mixing 1.3 M LiPF6 with a mixture solvent of ethylene carbonate (EC), methyl ethyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of about 3:4:3 was used.
[0204] Evaluation Example 1: Surface analysis of positive electrode active material
[0205] A scanning electron microscope (SEM) image of the first particles prepared in Preparation Example 1-1 (in a single particle form) is shown in Figure 8A A SEM image of the first particles prepared in Preparation Example 1-2 (in a secondary particle form) is shown in Figure 8B A SEM image of the second particles prepared in Preparation Example 1-3 is shown in Figure 9 A SEM image of the third particles prepared in Preparation Example 1-4 is shown in Figure 10
[0206] Referring to Figure 8A It can be confirmed that the first particles of Preparation Example 1-1 according to the present disclosure have a fine single particle form having a nanometer size. Referring to Figure 8B It can be confirmed that the first particles of Preparation Example 1-2 according to the present disclosure have a spherical secondary particle form in which a plurality of first primary particles are aggregated. In addition, it can be confirmed that the primary particles of Preparation Example 1-2 have a smaller size and are substantially more uniform than the primary particles of Preparation Example 1-1.
[0207] Referring to Figure 9 It can be confirmed that the second particles of Preparation Example 1-3 according to the present disclosure have a secondary particle form in which a plurality of second primary particles are aggregated.
[0208] Referring to Figure 10 It can be confirmed that the third particles of Preparation Example 1-4 according to the present disclosure have a single particle form.
[0209] Evaluation Example 2: Active Material Evaluation and Battery Evaluation of Main Active Material
[0210] The powder packing density (PD) of each of the main active materials of Preparation Example 2-3 and Preparation Example 2-4 and the characteristics of each of the rechargeable lithium batteries manufactured using the main active materials were evaluated. The powder packing density (PD) of each of the positive electrode active materials of Comparative Example 1 and Comparative Example 2 and the characteristics of each of the rechargeable lithium batteries manufactured using the positive electrode active materials were evaluated. Since the evaluation was performed to observe a change in characteristics depending on the Mn content (e.g., amount) in the main active material, the evaluation was performed without including the third particles PTC3.
[0211] At 25°C, each of the rechargeable lithium batteries was initially charged under constant current (about 0.2C) and constant voltage (about 4.25V, about 0.01C cutoff current) conditions, and after resting for about 10 minutes, discharged under constant current (about 0.2C) conditions to about 2.5V, to perform initial charging and discharging, to obtain initial charge capacity (0.2C charge amount) and initial discharge capacity (0.2C discharge amount), and efficiency (0.2C efficiency (%)) was expressed as initial charge capacity / initial discharge capacity. Then, charging and discharging was repeated 50 times at about 0.2C (about 4.25V, about 0.01C cutoff current) / 0.2C (about 2.5V, about 0.01C cutoff current), and life (% of 50 cycles) was expressed as discharge capacity after the 50th cycle / initial discharge capacity. Average voltage was obtained by integrating the area under the discharge voltage curve (voltage-capacity graph) after initial charging and discharging of the battery cell, and then dividing the integral by the discharge capacity. The results of the evaluation of the battery properties are shown in Table 1. The Mn content (e.g., amount) refers to the content (e.g., amount) of Mn with respect to the metal elements other than lithium in the main active material. Then, at 25°C, the battery was charged and discharged at a rate of 0.2C / 0.2C in a voltage range of 3.0V~4.45V to calculate the energy density. The energy density was obtained by using the following calculation equation: {average driving voltage (V) x capacity (Ah) / battery cell weight (kg)}, where the capacity was calculated by multiplying the positive electrode weight (g) by the discharge capacity (mAhg).
[0212] Table 1
[0213]
[0214] Referring to Table 1, it can be confirmed that each of the batteries according to Preparation Examples 2-3 and 2-4 has substantially the same efficiency as the batteries according to Comparative Examples 1 and 2. It can be confirmed that each of the batteries according to Preparation Examples 2-3 and 2-4 has a higher average voltage and a higher powder compaction density than the battery according to Comparative Example 1. It can be confirmed that each of the batteries according to Preparation Examples 2-3 and 2-4 has better life characteristics and a higher energy density than the battery according to Comparative Example 2. For example, it can be confirmed that if (e.g., when) the Mn content (e.g., amount) with respect to the metal elements other than lithium in the main active material is about 50mol%~about 70mol%, the decrease in efficiency and average voltage can be minimized or further decreased, while achieving excellent or appropriate life and excellent or appropriate energy density characteristics.
[0215] Evaluation Example 3: Evaluation of Positive Electrode Active Material
[0216] The powder packing density (PD) of each of the positive electrode active materials of Examples 1 to 4 and Reference Examples 3 and 4 was measured, and the results are shown in Table 2. The powder packing density was measured by placing 3 g of the positive electrode active material in a powder packing mold and applying a force of about 4.0 metric tons for about 30 seconds.
[0217] Table 2
[0218]
[0219] Referring to Table 2, it can be confirmed that the batteries according to Examples 1 and 2 of the present disclosure each have a higher powder packing density than the battery according to Reference Example 3. In addition, it can be confirmed that the batteries according to Examples 3 and 4 of the present disclosure each have a higher powder packing density than the battery according to Reference Example 4. For example, it can be confirmed that if the content (e.g., amount) of the third particles PTC3 is about 0.5 parts by weight to about 1 part by weight based on about 100 parts by weight of the positive electrode active material, the powder packing density is excellent or appropriate.
[0220] Evaluation Example 4: Battery Evaluation
[0221] The characteristics of each of the rechargeable lithium batteries manufactured using the positive electrode active materials of Examples 1 to 4 and Reference Examples 3 and 4, respectively, were evaluated, and the results are shown in Table 3. The evaluation conditions were the same as in Evaluation Example 2.
[0222] Table 3
[0223]
[0224] Referring to Table 3, it can be confirmed that the batteries according to Examples 1 and 2 each have the same or better efficiency and lifespan and substantially the same or higher energy density than the battery according to Reference Example 3. In addition, it can be confirmed that the batteries according to Examples 3 and 4 each have the same or better efficiency and lifespan and substantially the same energy density than the battery according to Reference Example 4. Further, it can be confirmed that the batteries according to Examples 3 and 4 each have better charge and discharge capacity, efficiency, lifespan, and energy density than the batteries according to Examples 1 and 2. For example, it can be confirmed that if (e.g., when) the first particles PTC1 contained in the positive electrode active material have a secondary particle form, better results are achieved than when the first particles PTC1 have a single particle form.
[0225] By including the olivine-based first particles, the positive electrode active material according to the present disclosure can exhibit improved economic feasibility, structural stability, and lifespan characteristics.
[0226] By including the spinel-based second particles, the positive electrode active material according to the present disclosure may exhibit improved average voltage.
[0227] The positive electrode active material according to the present disclosure may exhibit improved capacity and energy density by including a small amount of third particles serving as a sacrificial positive electrode.
[0228] By mixing the first particles, the second particles, and the third particles in a suitable or appropriate ratio, the positive electrode active material according to the present disclosure may have improved energy density and lifespan characteristics while ensuring economic feasibility.
[0229] As used herein, the term “main active material” refers to component active materials present in the main active material in a combined amount greater than at least 80 wt % or more of the total amount by weight of the electrode active material including the main active material.
[0230] In the present disclosure, expressions such as "at least one of," "one of," and "selected from," when preceding or following a list of elements, modify the entire list of elements and do not modify the individual elements of the list. For example, "at least one of a, b, and c" and "at least one selected from a through c" refer to only a, only b, only c, both a and b (e.g., simultaneously), both a and c (e.g., simultaneously), both b and c (e.g., simultaneously), all of a, b, and c, or variations thereof. As used herein, " / " may be interpreted as "and" or "or," as appropriate.
[0231] In the context of this disclosure, and unless otherwise defined, the terms "use," "using," and "used" may be considered synonymous with the terms "utilize," "utilizing," and "utilized," respectively.
[0232] In the present disclosure, the term "Group" as used herein refers to a Group of the Periodic Table of the Elements according to the Group 1 to 18 system of the International Union of Pure and Applied Chemistry ("IUPAC").
[0233] As used herein, the terms "substantially," "about," and similar terms are used as terms of approximation and not as terms of degree, and are intended to account for the inherent deviations in measured or calculated values that would be recognized by one of ordinary skill in the art. As used herein, "about" or "approximately" also include the stated value and mean within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the stated value.
[0234] Any numerical range recited herein is intended to include all sub-ranges of the same entire range. For example, a range of 1.0 to 10.0 is intended to include all sub-ranges, for example, 2.4 to 7.6, within the same entire range, i.e., having a minimum value of equal to or greater than 1.0 and a maximum value of equal to or less than 10.0. Any maximum numerical limitation recited herein is intended to include all lower numerical limitations subsumed therein and any minimum numerical limitation recited in this specification is intended to include all higher numerical limitations subsumed therein. Accordingly, Applicant reserves the right to amend this specification, including the claims, to expressly recite any sub-range subsumed within the ranges expressly recited in this specification.
[0235] The battery manufacturing apparatus, battery management system (BMS) apparatus, and / or any other related apparatus or components according to embodiments of the present disclosure described herein can be implemented with any suitable hardware, firmware (e.g., application specific integrated circuits), software, or a combination of software, firmware, and hardware. For example, various components of the apparatus can be formed on one integrated circuit (IC) chip or on separate IC chips. Further, various components of the apparatus can be implemented on a flexible printed circuit film, a tape carrier package (TCP), or a printed circuit board (PCB), or formed on one substrate. Further, various components of the apparatus can be processes or threads running on one or more processors in one or more computing devices, executing computer program instructions and interacting with other system components for performing the various functions described herein. The computer program instructions are stored in a memory that can be implemented in a computing device using a standard memory device, such as, for example, a random access memory (RAM). The computer program instructions can also be stored in other non-transitory computer readable media such as, for example, a CD-ROM, a flash drive, etc. Also, a person of ordinary skill in the art should recognize that the functions of the various computing devices can be combined or integrated into a single computing device, or the functions of a particular computing device can be distributed across one or more other computing devices, without departing from the scope of the present disclosure.
[0236] With the overall disclosure in mind, one of ordinary skill in the art will recognize that each appropriate feature of the various embodiments of the present disclosure can be combined in part or in whole with each other, and can be technically interlocked and operated in various appropriate manners, and each embodiment can be implemented independently of each other or in combination with each other in any appropriate manner, unless otherwise recited or implied.
[0237] While one or more embodiments of the present disclosure have been described, it is understood that the present disclosure should not be limited to these described embodiments, but rather modifications and alterations can be made by those having ordinary skill in the art within the spirit and scope of the claims and their equivalents.
Claims
1. A positive electrode active material, comprising: a plurality of first particles each including a compound represented by Chemical Formula 1 and having an olivine structure; a plurality of second particles each including a compound represented by Chemical Formula 2 and having a spinel structure; and a plurality of third particles each including a compound represented by Chemical Formula 3, wherein the first particles and the second particles constitute a main active material in an amount of 95 parts by weight to 99.5 parts by weight based on 100 parts by weight of the positive electrode active material, and the third particles are in an amount of 0.5 parts by weight to 5 parts by weight based on 100 parts by weight of the positive electrode active material, Chemical Formula 1 Chemical Formula 2 Li a1 Fe x1 B 1 y1 PO 4-b1 , In Chemical Formula 1, 0.8≤a1≤1.2, 0.95≤x1≤1.0, 0≤y1≤0.05, 0≤b1≤0.05, x1+y1=1, and B 1 comprising at least one element selected from the group consisting of Al, Ti, V, and Mg, Chemical Formula 3 Li a2 Mn x2 C 1 y2 O 4-b2 , In Chemical Formula 2, 0.8≤a2≤1.2, 1.9≤x2≤2.05, 0≤y2≤0.05, 0≤b2≤0.05, and C 1 comprises at least one element selected from the group consisting of Al and Mg, and 2.The positive electrode active material of claim 1, wherein the main active material has an amount of Mn of 50 mol% to 70 mol% based on metal elements other than lithium in the main active material. Li a3 Co x3 D 1 y3 O 4-b3 , In Chemical Formula 3, 5.9 < a3 ≤ 6.1, 0.9 ≤ x3 ≤ 1.05, 0 ≤ y3 ≤ 0.05, 0 ≤ b3 ≤ 0.05, and D 1 includes at least one element selected from the group consisting of Al and Mg. 3.The positive electrode active material of claim 1, wherein a mixing ratio by weight of the first particles to the second particles is 55:45 to 37:
63. 4.The positive electrode active material of claim 1, wherein the third particles are in an amount of 0.5 parts by weight to 1 part by weight based on 100 parts by weight of the positive electrode active material. 5.The positive electrode active material of claim 1, wherein the third particles are configured to be electrochemically deactivated after a first cycle. 6.The positive electrode active material of claim 1, wherein the first particles have a single particle form, the first particles include one or more first primary particles, a first average particle diameter of the first particles is 0.5 µm to 2.5 µm, and an average size of the first primary particles is 200 nm to 300 nm. 7.The positive electrode active material of claim 1, wherein the first particles include a plurality of first primary particles aggregated with each other, and the second particles include one or more second primary particles. 8.The positive electrode active material of claim 7, wherein a first average particle diameter of the first particles is 3 µm to 10 µm, and an average size of the first primary particles is 100 nm to 200 nm. 9.The positive electrode active material of claim 7, wherein the average size of the first primary particles is smaller than an average size of the second primary particles. 10.The positive electrode active material of claim 7, wherein an average size of the second primary particles is 0.5 µm to 3 µm. 11.The positive electrode active material of claim 1, wherein the first particles include a first coating layer containing a carbon element, and an amount of the carbon element in the first particles is 1.5 wt% to 2.5 wt% based on a total weight of 100 wt% of the first particles. 12.The positive electrode active material of claim 1, wherein the third particles have a single particle form. 13. The positive electrode active material of claim 1, wherein the porosity of the first particles is 20% to 40% when the first particles have a secondary particle form, and the porosity of the first particles is less than 30% when the first particles have a single particle form.
14. The positive electrode active material of claim 1, wherein the span value of the first particles measured by a particle size analyzer is 0.3 to 0.
75.
15. A positive electrode comprising: a positive electrode current collector; and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 14, a conductive material, and a binder, and the positive electrode is used for a rechargeable lithium battery.
16. The positive electrode of claim 15, wherein the amount of the binder is 0.5 parts by weight to 5 parts by weight based on 100 parts by weight of the positive electrode active material layer.
17. The positive electrode of claim 15, wherein the binder comprises at least one selected from the group consisting of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, an oxirane-containing polymer, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, and nylon.
18. The positive electrode of claim 15, wherein the amount of the conductive material is 0.5 parts by weight to 5 parts by weight based on 100 parts by weight of the positive electrode active material layer.
19. The positive electrode of claim 15, wherein the conductive material comprises a carbon-based material, a metal-based material having a metal powder form or a metal fiber form, a conductive polymer, or a mixture thereof.
20. A rechargeable lithium battery comprising the positive electrode according to any one of claims 15 to 19.
Citation Information
Patent Citations
A circular duct manufacturing apparatus
KR1020240054514A